The velocity and acceleration of length growth of a fresh water major carp of India, Catla catla spawned in two rearing conditions - Basu, T K; Bhattacharyya, B (Indian Journal of Fisheries, 2011)
Two popular methodological techniques, autoregressive and finite difference methods were employed simultaneously to analyse growth data of Catla catla (Ham.) spawn procured from artificial and semi natural incubating systems. The experimental results indicated a preponderance of semi natural incubating system over its counterpart as far as length increments of 50 spawn over a 24-day period of observations were concerned. It was also revealed that both the methodologies can be used with precision for the purpose of curve fitting.